Land banking as an asset class for retail investors. - Foo, Leon Cher Xiang. (2008)
In light of the recent emergence of land banking companies in Singapore, this report seeks to help retail investors better understand the mechanics of land banking and examines the conditions conducive for it. We further explore the common misconception regarding Reits as being similar to land banking and help differentiate between the two.